Solar cooking - Waring, Rob (Australia : Heinle, Cengage Learning, 2009)
A group of people has developed an efficient, healthy way to cook using the sun. Solar cooking is good for the environment and is also extremely helpful to people in certain countries
'National geographic' - cover
Book is accompanied by one DVD, entitled'Solar cooking' bearing the same call number and available at Bahagian Koleksi Media
Keywords: English language -- Textbooks for foreign speakers; Solar cookery